PENGARUH BUDGETARY GOAL CHARACTERISTICS PADA KINERJA MANAJERIAL DENGAN SELF-EFFICACY SEBAGAI VARIABEL MODERASI - Prayoga, Kadek Dias; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 21 No 3 (2017), 2017)
Some previous studies on the effect of budgetary goal characteristics on both the private and public sectors on managerial performance show inconsistent results. This study aims to obtain empirical evidence on the influence of budgetary goal characteristics on managerial performance and test whether self-efficacy can act as a moderating variable. Managerial performance is the manager's operational results based on predetermined targets, standards, and criteria. Managerial performance will increase when managers have fulfilled management functions, comprising, planning functions, organizing functions, direction functions, and control functions. This study aims to prove empirically the influence of self-efficacy on the relationship between budgetary goal characteristics and managerial performance (empirical studies on local government Buleleng District). This research was conducted at Buleleng regency government through 38 Regional Devices (Perangkat Daerah / PD) in Buleleng Regency. The population of this study are officials in PD. The method of determining the sample of this study using purposive sampling method, with the number of samples of 50 respondents. Methods of data collection using survey methods and interviews using a questionnaire. Data analysis technique used in this research is technique of Moderated Regression Analysis (MRA). Based on the results of the research analysis, it is known that budgetary goal characteristics have a positive effect on managerial performance and self-efficacy able to moderate relationship between budgetary goal characteristics on managerial performance. Keywords: Budget, BGC , SE , Managerial Performance